2013
DOI: 10.1186/1742-4690-10-106
|View full text |Cite
|
Sign up to set email alerts
|

Expression profile of host restriction factors in HIV-1 elite controllers

Abstract: BackgroundSeveral host-encoded antiviral factors suppress HIV-1 replication in a cell-autonomous fashion in vitro. The relevance of these defenses to the control of HIV-1 in vivo remains to be elucidated. We hypothesized that cellular restriction of HIV-1 replication plays a significant role in the observed suppression of HIV-1 in "elite controllers", individuals who maintain undetectable levels of viremia in the absence of antiretroviral therapy (ART). We comprehensively compared the expression levels of 34 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
88
4
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 84 publications
(103 citation statements)
references
References 54 publications
10
88
4
1
Order By: Relevance
“…The contribution of non-cell-intrinsic mechanisms to IFN-␣ anti-HIV-1 effects should be explored in greater detail. These data support the concept that the induction of particular intrinsic immune mechanisms may constitute a promising antiretroviral strategy, complementing our previous in vitro work (21) and our translational studies of restriction mechanisms in HLA-B*57-positive individuals (22) and HIV-1 elite controllers (11).…”
supporting
confidence: 72%
See 1 more Smart Citation
“…The contribution of non-cell-intrinsic mechanisms to IFN-␣ anti-HIV-1 effects should be explored in greater detail. These data support the concept that the induction of particular intrinsic immune mechanisms may constitute a promising antiretroviral strategy, complementing our previous in vitro work (21) and our translational studies of restriction mechanisms in HLA-B*57-positive individuals (22) and HIV-1 elite controllers (11).…”
supporting
confidence: 72%
“…We designed and implemented a custom TLDA to measure the expression of 34 anti-HIV-1 restriction genes (11). We relied on the following two minimal criteria for inclusion in our CuRe TLDA: (i) peer-reviewed, published evidence of direct inhibition of HIV-1 replication in vitro and (ii) detectable expression in human peripheral blood mononuclear cells.…”
mentioning
confidence: 99%
“…More recently, we comprehensively quantified the overall restriction factor expression profile of primary cells in healthy individuals and demonstrated that cellular activation strongly induced the expression of anti-HIV-1 genes and that increased gene expression correlated with decreased ex vivo HIV-1 replication (11). We have also used this platform to analyze host restriction factor gene expression in a cross-sectional study of HIV-1 patients at different stages of disease (13).…”
mentioning
confidence: 99%
“…We quantified the expression of 32 different anti-HIV-1 genes using a custom-made TaqMan array (11,13) and measured the levels of CD4 ϩ T cell activation over 7 years. We found that overall, restriction factor gene expression consistently increased over time and was significantly associated with systemic CD4 ϩ T cell activation and viral load.…”
mentioning
confidence: 99%
“…We utilized latency models to obtain unique mechanistic insights into the role of intrinsic cellular immunity during ART. Previous work by our group led to the development of a quantitative PCR-based (qPCR-based) array capable of examining the expression of a predefined set of antiviral genes in primary cells (12,21). In this work, we hypothesized that transcriptional HIV-1 persistence in latent reservoirs during antiretroviral therapy (ART) is the main obstacle to virus eradication.…”
Section: Introductionmentioning
confidence: 99%